Analisis Faktor-Faktor Yang Mempengaruhi PergantianKantor Akuntan Publik (KAP) Pada PerusahaanManufaktur Yang Terdaftar Di Bursa Efek Indonesia(Bei) Periode 2011-2014 - Chandra A S, Ria, Drs.Wahyono, Ak,MA (2016)
This study is aimed to analyze the effect of the change of Going Concern Opinion KAP, to analyze the effect of Auditor Reputation effect the turn of KAP, to analyze the effect of the change of KAP Financial Distress, to analyze the effect of the change of KAP Substitution Management, The population in this research is manufacturing companies listed in Bursa Efek Indonesia (BEI) during the period 2011-2014. The sample in this research manufacturing companies listed in Indonesia Stock Exchange during the period 2011-2014. Based on this research, going concern opinion variable affect on the turning of KAP, variable auditor reputation does not affect the change of KAP, variable financial distress does not affect the change of KAP variable management changes did not affect the change of KAP.